Midwifery practice : unfettered or shackled? : a thesis submitted in partial fulfilment of the requirements for the degree of Master Arts in Nursing, Massey University - Moloney, Jocelyn A (Massey University, 1992)
This thesis examines the ways that neophyte midwives experience their everyday practice world. The critical reflexive analysis of the perceptions of five practising midwives illustrate how socially generated constraints function to restrict professional midwifery care. This approach directs attention toward generating emancipatory knowledge which may assist midwives to overcome some of the contradictory and constraining conditions of their practice. The theoretical assumptions of critical social science expose for critique the ways in which socio-political forces constrain individual and professional action. There is an underlying assumption that the collaborative nature of the research process will enable midwives to make deliberate choices between alternative courses of action. This may be achieved by subjecting values and intentions to inquiry in the light of structural constraints on individual practice situations. The study is particularly timely when legislative changes continue to contribute to the changing context of midwifery practice. The research process and the findings of this study may provide the basis for an ongoing open-ended dialogue and critique so that midwives may be enabled to transform their practice world through collective action. Although political action was not demonstrated in the time frame of this study, it is argued that engaging participants in critique will provide the basis for an ongoing liberating effect toward autonomy and self-determination in midwifery practice.
Keywords: Midwives' attitudes; Maternity nursing; Midwifery, New Zealand